2018
DOI: 10.1111/ijd.14048
|View full text |Cite
|
Sign up to set email alerts
|

Hypohidrotic ectodermal dysplasia: clinical and molecular review

Abstract: Hypohidrotic Ectodermal Dysplasia (HED) is a genetic human disorder which affects structures of ectodermal origin. Although there are autosomal recessive and dominant forms, X-linked (XL) is the most frequent form of the disease. This XL-HED phenotype is associated with mutations in the gene encoding the transmembrane protein ectodysplasin-1 (EDA1), a member of the TNFα-related signaling pathway. The proteins from this pathway are involved in signal transduction from ectoderm to mesenchyme leading to the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 42 publications
2
64
0
3
Order By: Relevance
“…Ectodermal dysplasias (ED) are a family of disorders characterized by aplasia or dysplasia of two or more ectoderm‐derived structures such as hair, teeth, nails and sweat glands. Hypohidrotic and anihidrotic ED, the most common forms of ED are characterized by the triad of hypotrichosis, hypodontia/oligodontia, abnormally shaped teeth and reduced ability to sweat (hypohidrosis) . Hypohidrotic ED is genetically heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectodermal dysplasias (ED) are a family of disorders characterized by aplasia or dysplasia of two or more ectoderm‐derived structures such as hair, teeth, nails and sweat glands. Hypohidrotic and anihidrotic ED, the most common forms of ED are characterized by the triad of hypotrichosis, hypodontia/oligodontia, abnormally shaped teeth and reduced ability to sweat (hypohidrosis) . Hypohidrotic ED is genetically heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…When activated, the IKK complex releases the transcriptional activator NF‐κB causing upregulation of the NF‐κB signaling pathway . Variants in EDA cause X‐linked ED and variants in EDAR or EDARADD cause both autosomal recessive (AR) and autosomal dominant (AD) forms …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that dental caries is caused by enamel defects or salivary gland malfunction. Numerous clinical studies have previously described the possible relationship between enamel defects and HED (AlNuaimi & Mansoor, 2019; Ambarkova, Jovanovska, Bajraktarova, Batra, & Popovski, 2017; Reyes‐Reali et al., 2018; Rojas & da Silva, 2015). An in vitro study using rat dental epithelial stem cells indicated that NF‐κB is involved in regulating the expression of amelogenesis‐related proteins (Liang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The ectodysplasin-A (Eda) pathway is known to be involved in the formation of several ectodermal organs, including hair and mammary glands (Mikkola, 2008), but has not been extensively studied in the LG context (Pispa et al, 2003). Eda loss-of-function (Eda −/− ) mutation in mammals, which leads to X-linked hypohidrotic ectodermal dysplasia (XLHED, MIM 305100) in humans (Bayés et al, 1998;Headon et al, 2001;Kowalczyk et al, 2011;Srivastava et al, 1997), is characterized by severe symptoms, including hair, tooth, sweat gland and salivary gland hypoplasia (for reviews, see Lefebvre and Mikkola, 2014;Reyes-Reali et al, 2018). Moreover, LG defects in XLHED patients lead to dry eye diseases (Dietz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%